2010
DOI: 10.1021/ie101050k
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Solvent-Pretreated Polyimide Nanofiltration Membranes for Separation of Dissolved Dyes from Toluene

Abstract: The major problem reported for commercially available membranes is their limited chemical stability in organic solvents. This article reports the influence of organic solvents with different polarity (methanol, acetone, acetic acid, toluene, and n-hexane) on the filtration performance of STARMEM membranes. These membranes are specified to be compatible with the solvents used. The pure toluene flux of these membranes and the rejection of azo dyes (Sudan Black and Rhodanile Blue) were measured before and after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 54 publications
1
25
0
1
Order By: Relevance
“…All membranes were immersed for 24 h with pure solvents of decreasing polarities (ethanol, isopropanol and n-hexane). Darvishmanesh et al [11] used nanofiltration and reverse osmosis commercial membranes (made of polyamide (PA), polyethersulfone (PES) and sulfonated polyethersulfone) and pretreatment in ethanol for at least 24 h. Darvishmanesh et al [12] used immersion treatments in various organic solvents for one week before permeation in nanofiltration membranes produced with PA. Van der Bruggen et al [13] also reported on their work with NF membranes, treatments of 24 h by immersion in ethanol and nhexane. All the authors noted improvements in the permeate flux after the pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…All membranes were immersed for 24 h with pure solvents of decreasing polarities (ethanol, isopropanol and n-hexane). Darvishmanesh et al [11] used nanofiltration and reverse osmosis commercial membranes (made of polyamide (PA), polyethersulfone (PES) and sulfonated polyethersulfone) and pretreatment in ethanol for at least 24 h. Darvishmanesh et al [12] used immersion treatments in various organic solvents for one week before permeation in nanofiltration membranes produced with PA. Van der Bruggen et al [13] also reported on their work with NF membranes, treatments of 24 h by immersion in ethanol and nhexane. All the authors noted improvements in the permeate flux after the pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…24,125,128,129 When polymers swell, the reorganization of the molecular structure of the membrane affects the solvent flux. 138,142 Extensive swelling can decrease the selectivity and even cause the peeling of the top layer. Many reports have indicated that the solvent permeability was proportional to the swelling/viscosity.…”
Section: The Influencing Factors Of Solvent Transfer Through Polymerimentioning
confidence: 99%
“…There are strong intra-and intermolecular interactions, for example, hydrogen bonds, among PI segments. Consequently, membranes derived from PI materials generally possess small pore sizes or even dense nonporous structures and thus find applications typically in the fields such as gas separation, pervaporation and nanofiltration [3][4][5][6][7]. Moreover, high temperature up to 300-400 1C is frequently required for an imidization process to enhance the thermal stability and solvent resistance of PI membranes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, massive consumption of PI or its precursors as well as other organic solvents will be involved, which are considerably expensive and not environmentally benign. Considering higher cost of PI than many other membrane materials, like polyvinyldifluoride and polysulfone, which reduces its popularity in large-scale applications, [5][6][7][8]13] it is of great significance to fabricate composite membranes combining low quantity of PI precursors with costefficient macroporous substrate membranes of high compatibility. In this case, the pore sizes of the PI composite membranes can be flexibly tuned in a broad range and ultimately to extend their practical applications [3,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%